Crime networks in Vietnamese diasporas: the Czech Republic case - Nožina, Miroslav (Crime, law and social change, 2010)
The study seeks to analyse the structure and "modus operandi" of crime networks in the Czech Republic´s Vietnamese diaspora. Vietnamese criminality in the country has roots in communist era. After the democratic changes at the end of 80s, it has been representing dynamically developing phenomena, penetrating not only the local Vietnamese emigrant community but the state apparatus as well. Actually, the Vietnamese criminal underground lives in a specific symbiosis with the local Asian emigrant community, where legal and illegal activities are frequently merged together. "Respectable men" who have features of both legal businessmen and criminal bosses are the main actors in these processes. They create parallel power structures in closed worlds of Asian emigrants.